PELAKSANAAN PENYIDIKAN TERHADAP PELAKU TINDAK PIDANA NARKOTIKA DI SATUAN NARKOTIKA POLRES BUKITTINGGI - Failin, Failin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Drugs on the one hand are drugs or materials used in the field of medicine or health care and development of science and on the other can also cause a very harmful dependence when abused or used Without strict and careful control and supervision. With the birth of Law No. 35 year 2009 concerning narcotics, all actions that export, import, produce, plant, store, circulate and or use narcotics and its sankations have been governed therein To mitigate and eradicate such crimes. The use of narcotics without strict control and supervision is very detrimental and is a huge danger to the human life, society, nation, and state and national resilience of Indonesia. When order in Bukittinggi police from year to year the figure of narcotic criminal offence increased, overall the case reached level P 21. So the implementation of narcotics investigation in Bukittinggi police is now running according to the rules, namely based on KUHAP, but the implementation is not effective because in this case still found inhibitory factors Implementation of the investigation, so that the implementation of effective investigation is not implemented.